The effect of positive expiratory pressure (PEP) therapy on symptoms, quality of life and incidence of re-exacerbation in patients with acute exacerbations of chronic obstructive pulmonary disease: a multicentre, randomised controlled trial. Issue 2 (4th September 2013) - Osadnik, Christian R; McDonald, Christine F; Miller, Belinda R; Hill, Catherine J; Tarrant, Ben; Steward, Ranjana; Chao, Caroline; Stodden, Nicole; Oliveira, Cristino C; Gagliardi, Nadia; Holland, Anne E
Abstract : Background: Positive expiratory pressure (PEP) is a technique used to enhance sputum clearance during acute exacerbations of chronic obstructive pulmonary disease (AECOPD). The impact of PEP therapy during acute exacerbations on clinically important outcomes is not clear. This study sought to determine the effect of PEP therapy on symptoms, quality of life and future exacerbations in patients with AECOPD. Methods: 90 inpatients (58 men; mean age 68.6 years, FEV1 40.8% predicted) with AECOPD and sputum expectoration were randomised to receive usual care (including physical exercise)±PEP therapy. The Breathlessness, Cough and Sputum Scale (BCSS), St George's Respiratory Questionnaire (SGRQ) and BODE index (Body mass index, airflow Obstruction, Dyspnoea, Exercise tolerance) were measured at discharge, 8 weeks and 6 months following discharge, and analysed via linear mixed models. Exacerbations and hospitalisations were recorded using home diaries. Results: There were no significant between-group differences over time for BCSS score [mean (SE) at discharge 5.2 (0.4) vs 5.0 (0.4) for PEP and control group, respectively; p=0.978] or SGRQ total score [41.6 (2.6) vs 40.8 (2.8) at 8 weeks, p=0.872]. Dyspnoea improved more rapidly in the PEP group over the first 8 weeks (p=0.006), however these benefits were not observed at 6 months. Exacerbations (p=0.986) and hospitalisations (p=0.359) did not differ between groups. Conclusions: We found no evidence that PEP therapy during AECOPD improves important short-term or long-term outcomes. There does not appear to be a routine role for PEP therapy in the management of such individuals.